An overview of the efficacy and signaling pathways activated by stem cell-derived extracellular vesicles in diabetic kidney disease - Lin, Yongda; Yang, Qian; Wang, Jiali; Chen, Xiutian; Liu, Yiping; Zhou, Tianbiao (Frontiers in Endocrinology, 2022)
Diabetic kidney disease (DKD) is one of the most common microvascular complications of diabetes mellitus and the most common cause of end-stage chronic kidney disease (ESRD). Controlling serum glucose remains the primary approach to preventing and slowing the progression of DKD. Despite considerable efforts to control diabetes, people with diabetes develop not only DKD but also ESRD. The pathogenesis of DKD is very complex, and current studies have shown that mesenchymal stromal cells (MSCs) regulate complex disease processes by inhibiting multiple pathogenic pathways and promoting pro-regenerative mechanisms. Extracellular vesicles (EVs) are products of MSCs. Current data indicate that MSC-EVs-based interventions not only protect renal cells, including podocytes, mesangial cells and renal tubular epithelial cells, but also improve renal function and reduce damage in diabetic animals. As an increasing number of clinical studies have confirmed, MSC-EVs may be an effective way to treat DKD. This review explores the potential efficacy and signaling pathways of MSC-EVs in the treatment of DKD.